(untitled) (REMUNOM, 2025)
Higher education plays a fundamental role in promoting a sustainable transition and transforming society. One of the main challenges facing universities is to train professionals with a profile in tune with social demands. In the midst of this dilemma, there is a need to reformulate the structure of professional training, in order to move towards solidifying theoretical and practical knowledge in a systemic and committed vision. Generally speaking, employability is based on the ability to move around and knowledge of market demands. The more adapted the professional, the greater their employability. This demand for qualifications reflects the need to adapt to the new demands and dynamics of the sector, highlighting the importance of solid, up-to-date training. This study analyzed the demands of the job market, identifying gaps and opportunities for improvement in academic training, with a view to increasing adaptation to the demands of the sector. The proposed methodology used the survey technique, through the application of forms to companies in need of professionals in the area. The research found that there is a significant gap between academic training and professional requirements. Companies currently attach great importance to behavioral skills, the so-called soft skills, because individuals with these characteristics are more flexible and adaptable to different environments. The need to constantly adapt agronomy training to the demands of the job market has also been proven. Higher education institutions, such as IFTO, play a fundamental role in this process, seeking to offer their students a solid and complete education that prepares them for the challenges of the professional world.